2011
DOI: 10.1152/japplphysiol.00912.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular responses to mental stress in prehypertensive humans

Abstract: Neurovascular responses to mental stress have been linked to several cardiovascular diseases, including hypertension. Mean arterial pressure (MAP), muscle sympathetic nerve activity (MSNA), and forearm vascular responses to mental stress are well documented in normotensive (NT) subjects, but responses in prehypertensive (PHT) subjects remain unclear. We tested the hypothesis that PHT would elicit a more dramatic increase of MAP during mental stress via augmented MSNA and blunted forearm vascular conductance (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
32
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 32 publications
7
32
1
1
Order By: Relevance
“…Mental arithmetic has been shown to cause a rise in MAP and muscle sympathetic nerve activity (MSNA) (25) and vasodilatation in forearm skeletal muscle (26). In our study, none of the cardiovascular parameters other than HR, DBP, and SV were affected, suggesting that the level of stress to this test was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Mental arithmetic has been shown to cause a rise in MAP and muscle sympathetic nerve activity (MSNA) (25) and vasodilatation in forearm skeletal muscle (26). In our study, none of the cardiovascular parameters other than HR, DBP, and SV were affected, suggesting that the level of stress to this test was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…6 Forearm responses to mental stress have previously been reported to be impaired in patients with essential hypertension (reduced increase in absolute FBF) and in prehypertension (reduced increase in forearm conductance) when compared with normotensive controls, 9,17 potentially implicating dysfunction of the nNOS pathway in essential hypertension. Because nNOS is responsible for tonic vasodilation under resting conditions, 6 this could also contribute to increased basal vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that altered limb vascular responsiveness to mental stress may also play an important role in the pathogenesis of hypertension. Specifically, it has been reported that forearm vasodilatory responses to mental stress are blunted in hypertensive (8) and prehypertensive (46,48) humans. Thus, investigations of limb vascular responsiveness to mental stress are clinically relevant.…”
mentioning
confidence: 99%